Boosting the input: 9‐month‐olds' sensitivity to low‐frequency phonotactic patterns in novel wordforms. (23rd July 2021) - Archer, Stephanie L.; Czarnecki, Natalia; Curtin, Suzanne
Abstract: To learn their first words, infants must attend to a variety of cues that signal word boundaries. One such cue infants might use is the language‐specific phonotactics to track legal combinations and positions of segments within a word. Studies have demonstrated that, when tested across statistically high and low phonotactics, infants repeatedly reject the low‐frequency wordforms. We explore whether the capacity to access low‐frequency phonotactic combinations is available at 9 months when pre‐exposed to wordforms containing statistically low combinations of segments. Using a modified head‐turn procedure, one group of infants was presented with nonwords with low‐frequency complex onsets ( dr ‐), and another group was presented with zero‐frequency onset nonwords ( dl ‐). Following pre‐exposure and familiarization, infants were then tested on their ability to segment nonwords that contained either the low‐ or the zero‐frequency onsets. Only infants in the low‐frequency condition were successful at the task, suggesting some experience with these onsets supports segmentation.